A kinetic analysis of the judo osoto-gari technique: relationship to sweeping leg velocity - Liu, L.; Deguchi, T.; Shiokawa, M.; Hamaguchi, K.; Shinya, M. (Sports Biomechanics, 2025)
The present study characterised supporting leg kinetics (sweeping and pivot legs) during osoto-gari and investigated the relationship between kinetic variables and sweeping leg velocity at sweep contact. Fifteen black belt judoka performed osoto-gari. Motion data were recorded using a Mac3D motion analysis system (250 Hz), and ground reaction force (GRF) data were collected using four force plates (1,000 Hz). During the swing phase, the peak anterior (r = -0.535, p = 0.040) and upward (r = -0.693, p = 0.005) GRFs generated by the sweeping leg and the peak plantar flexion moment (r = 0.548, p = 0.034) and power (r = -0.700, p < 0.005) of the sweeping leg ankle joint significantly correlated with the sweeping leg velocity at sweep contact. During the throwing phase, the peak clockwise moment (r = -0.604, p = 0.017) correlated with the peak sweeping leg velocity. The peak knee extension moment (r = 0.602, p = 0.018), hip flexion moment (r = -0.589, p = 0.021) and knee power (r = -0.618, p = 0.016) of the pivot leg also correlated with the sweeping leg velocity at sweep contact. The results indicated that exertion of the sweeping leg ankle plantar flexors positively contributed to the sweeping velocity. Increasing whole-body rotation by contracting the pivot leg knee extensors is a crucial biomechanical factor in accelerating the sweeping leg at sweep contact.